The Neotropical genus Lenkothrips (Thysanoptera: Heterothripidae): additions to the faunas of Argentina and Brazil with an updated key to species - Lima, Élison Fabrício B.; Zamar, María I.; Greco, Nancy; Rocca, Margarita (Zootaxa, 2024)
Lenkothrips is a Heterothripidae genus with five species known only from South America. These species breed exclusively on flowers and exhibit some degree of host specificity. In the present paper, we describe three further species from Argentina (L. moundi sp. n.) and Brazil (L. canastra sp. n. and L. pantanal sp. n.) and provide an updated key to the now eight species of Lenkothrips.